Fruit Zone : Media Pembelajaran Interaktif Pengenalan Buah Anak Kelompok Belajar Menggunakan ResNet18 - Komariah, Siti Ingefatul; Putri, Desti Fitri Aisyah; Rahmawati, Siska Yulia; Fitri, Zilvanhisna Emka; Atmadji, Ery Setiyawan Jullev; Widiastuti, Reski Yulina; Imron, Arizal Mujibtamala Nanda (LPPM, 2024)
Learning media is very important in supporting learning activities in early childhood. Limited learning media and learning methods that are still centered on the ability and experience of teachers are an obstacle to improving learning at Pos Alamanda 105 Jumerto, Jember. An interactive, cheap, easy and accessible learning media is needed to improve students' abilities, especially in fruit recognition using both Indonesian and English. The solution, researchers used Deep Learning method for interactive learning media of fruit introduction in early childhood. The method used is Convolutional Neural Network with Resnet18 architecture. This research uses 21 types of popular fruits and unique fruits equipped with voice features in Indonesian and English. The total data of 2100 fruit images with a learning rate of 0.0002 and a maximum epoch of 100 wereable to classify the fruit with an accuracy rate of 96% (system training) and 95% (system testing).